31. HYPERTENSION AND RISK OF MORTALITY IN STROKE JAVANESE PATIENTS IN NEURO HCU DR. MOEWARDI HOSPITAL SURAKARTA. (May 2021) - Hamidi, Baarid Luqman; Kirana, Dewi Hayu; Mirawati, Diah Kurnia; Danuaji, Rivan; Subandi,; Budianto, Pepi; Hambarsari, Yetty; Prabaningtyas, Hanindya
Abstract : Background: Worldwide, stroke is the second leading cause of death and the third leading cause of disability. According to WHO in 2016, 70% of stroke cases were found in low and middle income countries, 87% of deaths from stroke were also found in these countries. Objective: This study aims to determine the factors that influence the mortality of stroke patients. Method: This study was conducted on all stroke patients in the Neuro HCU Dr. Moewardi Hospital in the period January to June 2020. The independent variables were assessed for their effect on patient mortality using a quantitative observational analytic approach with logistic regression analysis. Results: There were 124 patients in this study. From eleven variables, only hypertension and stroke type passed the verification test. Further tests were carried out and it was found that patients with hypertension and subarachnoid hemorrhage (SAH) had the highest probability of mortality (0.888). Conclusion: The probability of mortality for hypertension and SAH in this study is in accordance with previous studies that hypertension increases the risk of mortality in stroke patients and SAH patients have high mortality and morbidity rates. Therefore, optimizing the management of blood pressure and SAH is needed to reduce the mortality of stroke patients.